MODERN INNOVATIVE TECHNOLOGIES IN SCIENCE LESSONS IN EDUCATIONAL ORGANISATION - Nurmakhanova Sholpan (Scientific Results, 2024)
The article examines modern innovative technologies in science lessons in educational organizations. The use of modern innovative technologies is discussed, which open up great opportunities for expanding the educational framework for each academic discipline.